Analisis Pengendalian Persediaan Bahan Baku pada Produksi Sandal di UD. Al Athyyah - Prananda Aditia Ramadan; Siti Mundari (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
UD. Al Athyyah is a sandal manufacturing company experiencing problems in raw material inventory control. Inaccurate raw material planning causes shortages and excess inventory, resulting in increased storage costs, disrupted production activities, and potential lost sales. This study aims to analyze raw material requirements using the Material Requirement Planning (MRP) method with lot sizing techniques, namely Lot For Lot (LFL), Economic Order Quantity (EOQ), and Period Order Quantity (POQ). The data used include product demand, product structure, raw material inventory, and lead time. The results show that the POQ method produces the lowest total inventory cost and helps the company improve inventory control efficiency while reducing the risk of raw material shortages.